The use of hydroxyethyl starch 200/0,5 as plasma subtitutes is safe in hypovolemic patients as indicated in changes of n-acetyl-ï¢-glucosaminidase and creatinin serum parameters - Shinta, Dewi Wara; Khotib, Junaidi; Rahardjo, Eddy; Rahmadi, Mahardian; Suprapti, Budi (Folia Medica Indonesiana, 2016)
Hydroxyethyl Starch (HES) is a compound that improves intravascular volume effectively and rapidly without causing tissue edema. However, HES also has renal safety profile which is still being debated. Based on clinical experience in Dr. Soetomo Hospital, the frequency of acute renal failure following HES 200/0.5 administration at a dose of less than 20 ml/kg (maximum dose) is very rare. The purpose of this study was to evaluate the effect of HES 200/0.5 at a dose of less than 20 ml/kg in patients undergoing surgery. N-acetyl-b-D-Glucosaminidase (NAG) per urine creatinine ratio and creatinine serum were used as main parameter to assess renal injury. This research was observational and prospective design in patients undergoing elective surgery at Gedung Bedah Pusat Terpadu, Dr. Soetomo Hospital, who requiring resuscitation therapy with HES 200/0.5 and met the inclusion and exclusion criteria. NAG was measured prior to surgery and 12 hours after administration of fluid therapy, while creatinine serum was observed before surgery and 48 hours after resuscitation. This study was conducted for three months, and obtained 50 subjects divided into 2 groups, crystalloid group and HES 200/0.5 group. Demographic and baseline characteristics did not differ between groups, except the total bleeding volume. Total bleeding in HES 200/0.5group was higher than crystalloid group (p <0.0001). The mean volume of fluid received in HES 200/0.5 group was 2042.0 ± 673.9 mL, higher when compared with that of crystalloid group (910.0 ± 592.0 ml). Doses of HES 200/0.5 received was 8.31 ± 4.86 ml/kg. Measurement of the of NAG/creatinine ratio and creatinine serum showed significant increase in both groups, but still within the normal range. In addition, the value of these two parameters did not differ between groups. In conclusion, HES 200/0.5 in a dose of less than 20 ml/kg is safe to use in patients who suffered from hypovolemic hemorrhage, without prior history of renal impairment.